Penggunaan Model Pembelajaran Radec dalam Keterampilan Berpikir Kritis di Sekolah Dasar - Yulita Dwi Lestari; Ridho Agung Juwantara; Riska Alfiawati; Deviyanti Pangestu; Chelsi Yuliana (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2026)
The RADEC learning model is an alternative model that can be used by teachers to improve critical thinking skills. This study aims to describe critical thinking skills in science learning using the RADEC learning model in elementary schools. This research method uses the Systematic Literature Review Method. This study carried out several stages, namely the identification stage, the selection stage, the verification stage, the combination stage, and the conclusion stage. The results of the study show that the articles obtained by the researcher were 11 articles that were in accordance with the research theme. The articles selected and considered relevant to this study consisted of articles published in 2021 totaling 2 articles, 2022 totaling 4 articles, 2023 totaling 2 articles, and 2024 totaling 3 articles. Critical thinking skills in science learning can be created through the stages of RADEC learning. These stages are the Read, Answer, Discuss, Explain, and Create stages. The researcher divided the discussion based on themes. These themes are (1) the RADEC learning model, (2) the RADEC learning model in science learning, and (3) the RADEC learning model in improving critical thinking skills.